Ethical and Sustainable Quantum Computing: Conceptual Model and Implications - Saurabh, Kumar; Yashika,; Rustagi, Varsha (The journal of contemporary issues in business and government, 2022)
Today, computing power is advancing with significant transformation in quantum technologies and provides state-of-the-art functionalities for next-generation digital solutions. At the same time, computing capabilities are influencing the various spheres of humanity while touching the operating models and end-user experiences. The advent of quantum computing raised many questions about the system design, development, implementation, and associated risks for human beings and species. The questions raised the call for a conceptual model to study ethics and quantum computing as a whole. The primary objective of the research is to develop a conceptual ethical and sustainable quantum computing model to investigate the ethics standards, trust levels, social aspects, access rights, privacy, moral and good-duties issues based on the current situations. The paper adopts the literature survey approach based on existing business ethics models to evaluate the model's human, organisation (society) and opportunity factors. The research has investigated the ethical constitutes of quantum computing led digital transformation. The research findings provide the substantial foundations for the research and managerial applicability to integrate the social, human, technology-based inclusive, ethical issues.